Raising Government Children : A History of Foster Care and the American Welfare State - Rymph, Catherine E. (Book collections on Project MUSE., 2018)
Tracing the evolution of the modern American foster care system from its inception in the 1930s through the 1970s, Catherine Rymph argues that deeply gendered, domestic ideals, implicit assumptions about the relative value of poor children, and the complex public/private nature of American welfare provision fuelled the cultural resistance to funding maternal and parental care.